Pengujian kekhususan inang parasitoid Anagyrus lopezi (De Santis) (Hymenoptera: Encyrtidae) pada empat spesies kutu putih yang berasosiasi dengan tanaman singkong - Rani Dessy Karyani; Nina Maryana; Aunu Rauf (Perhimpunan Entomologi Indonesia, 2016)
A parasitoid, Anagyrus lopezi (De Santis) (Hymenoptera: Encyrtidae) was introduced from Thailand into Indonesia in early 2014 to control the cassava mealybug Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae). To determine its potential uses and effect on non-target species, behavioural observation of the parasitoids were made on four species of mealybugs, i.e. P. manihoti, Paracoccus marginatus Williams-Granara de Willink, Pseudococcus jackbeardsleyi Gimpel-Miller, and Ferrisia virgata Cockerell (Hemiptera: Pseudococcidae). For that purposes, a set of tests were conducted which includes host susceptability, preference, and suitability. Tests were conducted by exposing a female parasitoid to 3rd instar nymphs of each mealybug species in a petri dish. For susceptability test, parasitoid A. lopezi encounterend P. manihoti more often (13.70 ± 7.18 visits per 30 minutes) as compared to P. marginatus (985 ± 10.24), P. jackbeardsleyi (6.60 ± 3.62), and F. virgata (5.75 ± 4.09). So did ovipositor probing occurred more on P. manihoti (8.20 ± 5.68 probes per 30 minutes) than on P. marginatus (0.70 ± 1.84), P. jackbeardsleyi (0.35 ± 0.68), and F. virgata (0.10 ± 0.45). For preference test, host encounter and ovipositor probing by the parasitoid were more common on P. manihoti as opposed to other mealybug species. Out of four mealybug species tested, P. manihoti was the only suitable host for parasitoid development, with the number of progenies emerged 7.40 ± 2.17 individuals per 3 female parasitoids exposed in 24 hour. Host specifity exhibited by parasitoid A. lopezi may prevent adverse effect to other mealybug species inhabiting cassava fields.